The spiffiest giant in town - Donaldson, Julia; Scheffler, Axel (New York : Puffin Books, 2005)
George the giant, known for wearing his old patched clothes, finally buys new ones, but then gives them away to some needy animals.
Booklist.
Publisher's Weekly.
School Library Journal.
3.6.
3.6
K-3
Keywords: Animals -- Fiction; Clothing and dress -- Fiction; Giants -- Fiction; Kindness -- Fiction; Animals -- Fiction; Clothing and dress -- Fiction; Giants -- Fiction; Kindness -- Fiction